Leveraging Social Networks for Cyber Threat Intelligence: Analyzing Attack Trends and TTPs in the Arab World - Seokhee Lee; Aisha Abdu Hassan Mujammami; Kyounggon Kim (IEEE Access)
The primary objective of this study is to investigate cybercrime threat intelligence in the context of attack trends and tactics, techniques, and procedures (TTPs) employed by cyber attack groups targeting the Arab world. Numerous scholarly papers have explored methods for collecting and extracting data from social networks, shedding light on the importance of cyber threat intelligence. In this paper, data were collected from X (former ‘Twitter’) using a script based on specific keywords. Our research underscores the widespread nature of social networks, where a wealth of information is disseminated, and a substantial number of threat information. Given that a considerable portion of these cybercrime threats are shared through social networks, making them a priority becomes crucial. The findings of our research highlight the importance of effectively using social networks in understanding and responding to cyber threats. The study contributes to improving cybersecurity in the Arab region by providing information on the dynamics of cyber threats and the method of operation of attack groups. It emphasizes the critical role of social networks in contemporary cyber-attack landscapes, offering practical implications for cybersecurity practitioners, law enforcement agencies, and policymakers committed to securing the digital environment in Arab nations.